Enhancing Teacher Competence in Learning Design through LMS-Based CMC Training Model with MKPS Flow: A School Supervisor-Led Approach - Karyat Heryana; Sumarto Sumarto; Asep Suryana; Cepi Triatna (AL-ISHLAH: Jurnal Pendidikan, 2024)
Teacher competence is a critical factor in educational success, yet traditional training methods often lack interactive and contextual relevance. This study aimed to improve teacher competence by developing a novel training model facilitated by school supervisors. Employing a research and development (RD) methodology, the study involved 15 teachers: 3 for small-group trials and 12 for large-group trials. Data were collected through interviews, observations, questionnaires, and Focus Group Discussions (FGDs). The research procedure included an analysis of current training practices, literature review on LMS-based Coaching, Mentoring, and Consulting (CMC) training using the MKPS flow, design and validation of the training model, iterative trials, and final model development. The study demonstrated that the LMS-based CMC training model effectively enhanced teacher competence. The model emphasized interactive mentoring by school supervisors and collaborative learning among teachers. It differed from conventional one-way training by fostering active engagement, contextual relevance, and problem-solving skills. The training addressed real-world challenges, enabling teachers to integrate learned skills into classroom practices. The CMC model promotes teacher reflection, independence, and continuous professional development. Unlike traditional methods, it encourages dynamic interaction and skill application in authentic teaching contexts, ensuring sustainability and relevance of the competencies developed. The LMS-based CMC training model provides a comprehensive and innovative approach to teacher development, supporting ongoing skill-building and collaboration, which are essential for long-term educational improvement.